Clinical Detection and Recovery of Vestibular and Oculomotor Impairments Among Amateur Athletes Following Sport-Related Concussion: A Prospective, Matched-Cohort Study. Issue 2 (2nd March 2021) - Büttner, Fionn; Howell, David R.; Doherty, Cailbhe; Blake, Catherine; Ryan, John; Delahunt, Eamonn
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To (1) quantify the diagnostic accuracy of the vestibular/oculomotor screening (VOMS), and (2) determine the recovery of vestibular and oculomotor impairments exhibited by concussed athletes compared with nonconcussed athletes using the VOMS. Setting: Clinical assessment laboratory. Participants: Amateur athletes who were diagnosed with sport-related concussion by emergency department physicians, and non-concussed, control athletes. Design: Prospective, longitudinal study. Main Measures: Participants were assessed 1 week following sport-related concussion, upon clearance to return-to-sporting activity, and 2 weeks following return-to-sporting activity by a study investigator who administered the VOMS. We calculated test sensitivity, specificity, and positive and negative predictive values to estimate the diagnostic accuracy of the VOMS. We performed a mixed-design analysis of variance to assess differences in VOMS symptom scores reported by concussed athletes compared with control athletes. Results: Fifty concussion participants and 50 control participants completed the study. The VOMS demonstrated sensitivity and specificity of 96% and 46%, respectively, and produced positive and negative predictive values of 64% and 92%, respectively. The concussion group exhibited a significantly greater symptom provocation change score from baseline than the control group for all test domains of the VOMS only in the first week following concussion. Conclusion: The VOMS may be most useful as a clinical screening tool to rule out, rather than confirm, the presence of sport-related concussion. The VOMS may be appropriate to inform the recovery of vestibular and oculomotor impairments exhibited by concussed individuals over time.